Meta‐analysis of the diagnostic accuracy of serum type IV collagen 7S concentration for the staging of liver fibrosis in nonalcoholic fatty liver disease. Issue 3 (29th November 2022) - Honda, Yasushi; Yoneda, Masato; Kobayashi, Takashi; Iwaki, Michihiro; Kawamura, Nobuyoshi; Nogami, Asako; Kessoku, Takaomi; Ogawa, Yuji; Tomeno, Wataru; Imajo, Kento; Horita, Nobuyuki; Saito, Satoru; et al.
Abstract: Aim: We aimed to evaluate the diagnostic accuracy of the measurement of serum type IV collagen 7S (T4C7S) concentration for the staging of liver fibrosis in patients with nonalcoholic fatty liver disease (NAFLD). Methods: A systematic search or published works was carried out using the PubMed, Cochrane Library, and Web of Science Core Collection databases for studies of the accuracy of serum T4C7S concentration for the staging of fibrosis using Fibrosis stage (F)0–4 in patients with NAFLD diagnosed by liver biopsy. Results: Nine articles describing 1475 participants with NAFLD were included. For fibrosis ≥F1, with n  = 849, summary estimates of sensitivity of 0.79, specificity of 0.69, and area under the curve (AUC) of 0.80 were obtained using a median T7C4S cut‐off value of 4.6 ng/ml. For fibrosis ≥F2, with n  = 1, 090, summary estimates of sensitivity of 0.78, specificity of 0.78, and AUC of 0.84 were obtained using a median cut‐off value of 4.9 ng/ml. For fibrosis ≥F3, with n  = 1311 participants and a median cut‐off value of 5.4 ng/ml, a pooled sensitivity of 0.82, specificity of 0.81, and AUC of 0.83 were obtained. For fibrosis ≥F4, with n  = 753 and a median cut‐off value of 6.6 ng/ml, a pooled sensitivity of 0.85, specificity of 0.81, and AUC of 0.85 were obtained. Conclusions: Serum T4C7S concentration was found to be an accurate method of staging liver fibrosis in patients with NAFLD.